Transparent organic materials of aircraft cockpit canopies: research status and development trends. (December 2015) - Wang, X. K.; Wei, S. C.; Xu, B. S.; Chen, Y.; Yan, X.; Xia, H. H.
Abstract : The characteristics of aircraft cockpit canopies made of transparent organic material are described. Three types of canopy and their characteristics are compared. The current status of cockpit canopy development in major industrial nations is compared. The typical performance characteristics of transparent materials for aviation applications are described. Future trends in the development of these transparent materials are discussed.